Objective assessment of the functional status of stroke patients: Can comprehensive rehabilitation treatment improve their functional efficiency? - Nowak Karina; Sobota Grzegorz; Sarzyńska-Długosz Iwona; Łukowicz Małgorzata; Nitera-Kowalik Agnieszka; Owsiński Robert; Bujalski Wiesław; Malec Agnieszka; Syczewska Małgorzata (Sciendo, 2022)
Study aim: To check if the short rehabilitation treatment (3 weeks) complemented by complex rehabilitation on advanced equipment improves the functional status of chronic stroke patients; and which clinical and objective parameters can be used to assess the efficacy of such treatment.